2021
DOI: 10.7717/peerj.10594
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hub genes and biological pathways in hepatocellular carcinoma by integrated bioinformatics analysis

Abstract: Background Hepatocellular carcinoma (HCC), the main type of liver cancer in human, is one of the most prevalent and deadly malignancies in the world. The present study aimed to identify hub genes and key biological pathways by integrated bioinformatics analysis. Methods A bioinformatics pipeline based on gene co-expression network (GCN) analysis was built to analyze the gene expression profile of HCC. Firstly, differentially expressed genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Drawing on the method of gene co-expression network construction [26,27], our distance between two genes was defined based on the Pearson correlation coefficient (Formula 1): where, g 1i denotes the expression level of gene 1 in the i th sample, g 1 denotes the mean expression level of gene 1 in all samples, and m denotes the number of samples. We ran the PAM with a range of different values (from 8 to 20) of cluster number k , and the k that optimized the Silhouette Score (Formula 2 ~ 3) was determined.…”
Section: Partitioning Around Medoidsmentioning
confidence: 99%
“…Drawing on the method of gene co-expression network construction [26,27], our distance between two genes was defined based on the Pearson correlation coefficient (Formula 1): where, g 1i denotes the expression level of gene 1 in the i th sample, g 1 denotes the mean expression level of gene 1 in all samples, and m denotes the number of samples. We ran the PAM with a range of different values (from 8 to 20) of cluster number k , and the k that optimized the Silhouette Score (Formula 2 ~ 3) was determined.…”
Section: Partitioning Around Medoidsmentioning
confidence: 99%
“…[10,11] Moreover, as a hub gene or candidate gene, NCAPD2 is involved in the invasion process of a variety of cancers and is a potential therapeutic target in hepatocellular carcinoma, gastric cancer, and ovarian cancer. [12][13][14] However, at present, the clinical application and functional mechanisms of NCAPD2 in LUAD remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al screened the genes and pathways associated with HCC development and prevalence through a series of bioinformatics observations, such as DEG recognition, functional enrichment analysis, PPI network and module analysis, and weighted network correlation analysis [ 24 ]. Zhou et al identified HCC critical genes and microRNAs through raw data processing by using Gene Ontology (GO), GEO2R, and Kyoto Encyclopaedia of Genes and Genomes (KEGG) pathway enrichment processing and PPI network creation [ 33 , 34 ]. Li et al identified 89 out of 320 consistent differentially expressed genes in HCC patients.…”
Section: Introductionmentioning
confidence: 99%